Hyperparathyroidism-Jaw Tumor Syndrome - Travis D. Weaver (Case Reports in Oncology, 2021)
Primary hyperparathyroidism is a relatively common endocrine disorder, affecting 7 out of 1,000 adults. The median age at onset is the 6th decade of life. Our objective was to present a young patient with primary hyperparathyroidism who has a positive CDC73 mutation. A 23-year-old woman was evaluated for hypercalcemia that was found after surgery for bilateral ovarian cyst removal. Her family history included multiple family members with nephrolithiasis. The physical examination revealed a well-appearing Caucasian woman with no palpable neck mass. The laboratory results showed serum calcium at 11.7 mg/dL (ref. 8.4–10.2), ionized calcium at 1.44 mmol/L (ref. 1.12–1.32), and serum PTH at 192 pg/mL (ref. 11–65). A technetium-99 sestamibi scan revealed focal uptake inferior to the left thyroid lobe. Thyroid ultrasound showed a left parathyroid adenoma. The patient subsequently underwent left inferior parathyroidectomy, which confirmed parathyroid adenoma, with resultant normalization of serum calcium and PTH levels. Due to her young age at diagnosis, genetic testing was performed, which revealed a mutation of CDC73. Although penetrance and expression are variable, the CDC73 mutation is associated primarily with hyperparathyroidism-jaw tumor syndrome, familial isolated hyperparathyroidism, and sporadic parathyroid carcinoma. This patient currently has no evidence of jaw, uterine or renal tumors on screening imaging. Given the potential impact of inheritable neoplasia, all young patients with unexplained hyperparathyroidism should be considered for genetic screening.